Analisis Faktor Penyebab Keterlambatan Proyek “XYZ” - Dwiantoro, Deny; Yoansa, Acep Yosep; Indrayana, Desiderius Viby; Mentari, Sekar; Widyatami, Filki Suri (Universitas Batanghari Jambi, 2024)
A project tends to experience delays if planning and control are not carried out properly. Various things can happen in a construction project that can cause an increase in processing time so that project completion is delayed. The purpose of this research is to identify and classify the factors that cause delays in the